CHARACTERISTICS OF HYDRAULIC JUMP ON A STRIPED CHANNEL BED - ALIL, SHAKER A. J; SARHAN, SARHAN A.; ALI, SIYAMAND M. (Journal of Duhok University, 2017)
The substantive conditions are affecting the subjective process of creating rapid turbulent changes in flow. Such character happens in hydraulic jump phenomenon, which depends on how much of flow kinetic energy changes into potential energy. During this process part of the kinetic energy is dissipated by taking other types of energy in the channel. The quantity of energy dissipated reflects on the height and length of the jump. The effects of lowering the bed of channel by means of square strips of six different spaces (2, 3, 4,5,6,7 cm) respectively are studied experimentally with additional smooth bed. The investigation leads that bed strips increases the energy dissipation by 6%. The energy dissipation increases with the increase of strips spacing, the best spacing is between 5 and 6 cm. Consequently jump height decreases which is reflected by the reduction of the relative sequent depth value by (6%-15%). While the relative length of jump decreases by 22% and 28% compared with the smooth bed. The mean dimensionless depth deficit is 0.15 and normalized jump length is 2.5. Within the limitations of this work, different relationships are suggested to predict hydraulic jump characteristics with coefficient of determination more than 0.9.